Development of the membrane ceiling method for in vitro spermatogenesis - Maki Kamoshita; Hiroki Shirai; Hiroko Nakamura; Tetsuya Kishimoto; Yuki Hatanaka; Daisuke Mashiko; Katsuhiro Esashika; Jingjing Yang; Satoshi Yamasaki; Takehiko Ogawa; Hiroshi Kimura; Masahito Ikawa (Scientific Reports)
Abstract Spermatogenesis is one of the most complex processes of cell differentiation and its failure is a major cause of male infertility. Therefore, a proper model that recapitulates spermatogenesis in vitro has been long sought out for basic and clinical research. Testis organ culture using the gas-liquid interphase method has been shown to support spermatogenesis in mice and rats. However, the conventional method using agarose gel has limitations including medium replacement efficiency and live imaging because agarose absorbs medium and is not transparent. To overcome this issue, we developed a new device using microporous membranes and oxygen-permeable materials. Mouse testes sandwiched between a microporous polyethylene terephthalate (PET) membrane on top and an oxygen-permeable 4-polymethyl-1-pentene polymer (PMP) membrane base maintained spermatogenesis over months. The chamber volume was minimized to 0.1% of the culture medium. Weekly time-lapse live imaging enabled us to observe transgenically fluorescent acrosome and nuclear shape formation throughout spermatogenesis. Finally, we obtained healthy fertile offspring from spermatozoa generated in our system. The device could be used not only for basic research to understand spermatogenesis but also for applied research, such as diagnosing and treating male infertility.